Editorial (Transactions of the Association of European Schools of Planning, 2018)
We are pleased to present the second issue of Transactions of the Association of the European Schools of Planning, the open-access, double-blind peer-reviewed journal of AESOP. In keeping with the journal’s aim, this issue brings together a variety of reflective and research papers, associated with AESOP events and activities.